Sosialisasi Pencegahan Penyakit Infeksi Kecacingan Di Wilayah Mataram - Ni Made Amelia Ratnata Dewi; Candra Eka Puspitasari; Nisa Isneni Hanifa (Universitas Mataram, 2020)
Abstract: Helminthiasis is an infection that often attacks children and could result in decreased health, nutrition, intelligence and productivity of the patient. The purpose of this community service activity is to organize a socialization that can improve the understanding of helminthiasis dangers and how to prevent it. The socialization method that used are presentation of the material by the speakers, discussions session and brochures distribution for the audition. The socialization was held in the South Batu Ringgit area. As many as 30 residents participated in this activity. The socialization went well and has produced the expected outcomes. Pre and post assesment to evaluate resident knowledge about helminthiasis were done by written multiple choice quiz. The difference between the pre-test and post-test score was carried out using the Wilcoxon test. Wilcoxon test results showed that there were significant differences between the pre-test and post-test with p values= 0.03 Keywords: infection, helminthiasis, socialization